2020
DOI: 10.1016/j.fuel.2020.118822
|View full text |Cite
|
Sign up to set email alerts
|

Gasification of biofuels blended from olive mill solid wastes and pine sawdust under different carbon dioxide/nitrogen atmospheres

Abstract: In this paper, we investigated the gasification of charcoals using a macro TG under CO 2 mixed with nitrogen at different percentages (40%, 70% and 100% CO 2 ) and at different fixed temperatures (750°C, 800°C, and 900°C). For this purpose, two raw residues were selected; the exhausted olive mill solid wastes (EOMSW) and the pine sawdust (PS). Then, four different samples, which have not been previously studied with a gasification process, were prepared from these residues when investigating the impregnated an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…Along with Syngas, various liquids composed of bio-oils and tars are also generated [75][76][77][78][79][80]. Hence, in this method of Syngas production, a large amount of CO 2 is used as a gasifier mixed or not with dry and heated water steam (at about 180°C) during the char gasification [75][76][77]80]. The formation of methane from CO 2 has been reported in previous studies [81].…”
Section: Co 2 As a Renewable Source Of Energy Via Biogas Productsmentioning
confidence: 75%
See 1 more Smart Citation
“…Along with Syngas, various liquids composed of bio-oils and tars are also generated [75][76][77][78][79][80]. Hence, in this method of Syngas production, a large amount of CO 2 is used as a gasifier mixed or not with dry and heated water steam (at about 180°C) during the char gasification [75][76][77]80]. The formation of methane from CO 2 has been reported in previous studies [81].…”
Section: Co 2 As a Renewable Source Of Energy Via Biogas Productsmentioning
confidence: 75%
“…The second process for biogas production is based on the thermochemical conversion of lignocellulosic biomass into a synthesis gas characterized by a high HHV called Syngas, which is a mixture of CO, H 2 , and C n H m mainly composed of CH 4 . Along with Syngas, various liquids composed of bio-oils and tars are also generated [75][76][77][78][79][80]. Hence, in this method of Syngas production, a large amount of CO 2 is used as a gasifier mixed or not with dry and heated water steam (at about 180°C) during the char gasification [75][76][77]80].…”
Section: Co 2 As a Renewable Source Of Energy Via Biogas Productsmentioning
confidence: 99%
“…In contrast, lithium is reinserted into the lithium layer at low voltage by further Mn +4 reduction (Figure 6b) [73,74]. The irreversible capacity loss that accounts for a value of approximately 50-100 mAh g -1 is attributed to the loss of lithium in the form of Li2O from the material surface and the formation of MnO2, which takes part in lithiation-delithiation in subsequent cycles [75][76][77]. Reproduced from reference [67].…”
Section: Lithiation-delithiation Mechanismmentioning
confidence: 99%
“…[19,[103][104][105][106][107][108][109]. Wu et al demonstrated that pristine Li[Li0.2Mn0.54Ni0.13Co0.13]O2, its modified versions such as 3 wt.% Al2O3, CeO2, ZrO2, ZnO, AlPO4 treated, and 0.05 Fatom per formula unit provides first discharge capacity of 253, 285, 253, 252, 252, 261, and 270 mAh g -1 , respectively and the first irreversible capacity of 75,41,36,48,58,22, and 58 mAh g -1 , respectively. The retention of oxide ion vacancies in the surface treated samples reduces the first cycle irreversible capacity loss and significantly modifies the first discharge capacity [110].…”
Section: Modificationmentioning
confidence: 99%
See 1 more Smart Citation